Viborgs første læger - og deres gravsten - Vellev, Jens (Kirkehistoriske Samlinger, 1989)
Starting from the restauration of the tombstone of the physician Johannes Paludan (1538-1615) the author describes the first physicians in Viborg. From the time of the reformation in 1536 until the introduction of the absolute monarchy in 1660 they were paid through some of the prelatures and canonicates of the cathedral prebends. Apart from their medical duties the physicians were members of the chapter, and consequently they were buried in the cathedral. To-day two tombstones have been preserved, the others are known from old manuscripts. After the restauration the highly fragmentary stone of Johannes Paludan has been measured, and through old descriptions and comparative studies the drawing has been complemented, so that a fairly reliable reproduction of the original appearance of the stone can be made. Paludan was physician in Viborg 1571-1615. His successors were his son Lucas Paludan (died 1638), Peder Iversen (died 1629), Christian Schytte (died 1650), Jacob Janus and finally Johan Christopher Creutzhauer (died 1692). Apart from the tombstone of Johannes Paludan only that of Christian Schytte has been preserved. However, the physicians’ burial places are known. They were placed mainly in the southern part of the cathedral: in the southern transept and in the Lady Chapel. The other parts of the building contained mostly tombs for the nobility of Jutland, their tombstones are quite a different story.